Impacts of Religious Beliefs on Environmental Indicators - Chuvieco, Emilio (Worldviews, 2016)
In this paper, the authors examine whether the more environmental-aggressive attitude of Christianity suggested by Lynn White (1967) could be sustained based on environmental indicators. The religious beliefs were obtained from a World database on religious practices, and the environmental variables from the Environmental Performance Index. Several controlling factors were generated to decouple the influence of religious traditions from other external variables, such as economic wealth or governance. The analysis was done worldwide at country level and for the African continent at provincial level. The results of our analysis demonstrate opposite trends to White’s conclusions, since Christian territories, both at country and provincial level, had better environmental indicators than territories dominated by other religious traditions, particularly compared to Muslim-dominant areas. Religious practice showed little explanatory power regarding environmental performance for all religions, although Christianity showed a higher positive correlation. Environmental performance of countries in all religious traditions showed a strong dependence from other controlling factors, particularly the human development index and the per capita income.